Upaya Pencegahan Kerusuhan di Rutan Kelas IIB Siak Sri Indrapura - Taqwa Ilahi, Abadi; Riky Novarizal (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2025)
This study aims to analyze the efforts to prevent riots at the Class IIB Detention Center (Rutan) in Siak Sri Indrapura using the Situational Crime Prevention approach. The research method used is qualitative, with data collected through interviews, observation, and documentation. Informants included structural prison officers, security guards, and inmates. The results show that the implementation of Situational Crime Prevention strategies, including increasing effort, increasing risk, and reducing provocation, has been effective in reducing the potential for riots. These strategies are implemented through strict supervision, controlled access, fulfillment of basic needs, and the provision of rehabilitation programs. However, challenges such as overcrowding, limited resources, and psychological factors among inmates remain and require further attention. This study provides practical contributions to prison security policy and theoretical contributions to the development of criminology.